Genetic differentiation between inshore and offshore populations of northern shrimp (Pandalus borealis). (20th September 2021) - Hansen, Agneta; Westgaard, Jon-Ivar; Søvik, Guldborg; Hanebrekke, Tanja; Nilssen, Einar Magnus; Jorde, Per Erik; Albretsen, Jon; Johansen, Torild
Abstract: Many marine organisms have a permanent presence both inshore and offshore and spawn in multiple areas, yet their status as separate populations or stocks remain unclear. This is the situation for the northern shrimp ( Pandalus borealis ) around the Arctic Ocean, which in northern Norway represents an important income for a small-scale coastal fishery and a large-vessel offshore fleet. In Norwegian waters, we uncovered two distinct genetic clusters, viz. a Norwegian coastal and a Barents Sea cluster. Shrimps with a mixed heritage from the Norwegian coastal and the Barents Sea clusters, and genetically different from both, inhabit the fjords at the northernmost coast (Finnmark). Genetic structure between fjords did not display any general trend, and only the Varangerfjord in eastern Finnmark displayed significant genetic structure within the fjord. Shrimps in the Finnmark fjords differed in some degree from shrimps both in the adjacent Barents Sea and along the rest of the coast and should probably be considered a separate management unit.